Re MA (Care Threshold): “Shocking” abuse followed by a “staggering” ruling on likely significant harm’ - Jane Williams (Family Law, 2010)
Critique of a decision made at first instance and by majority ruling in the Court of Appeal onthe application of the threshold of 'likely to suffer serious harm' in the Children Act 1989.